2017
DOI: 10.17349/jmc117310
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Differences and Technology Acceptance: A Comparative Study

Abstract: Research on the adoption and diffusion of new technology has long been of interest to IS researchers. As business globalization has increased, interest in IT adoption in cultures has increased. What aspects of adoption and diffusion are important to understand and acknowledge when considering IT adoption in countries that are culturally different? This paper provides a review of academic articles that have investigated adoption and diffusion around the world. A framework summarizing the main topics on cultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The findings of Kunze et al (2013) at least show that older employees were less resistant towards IT innovations than their younger colleagues. Similarly, differences in social and national culture were also shown to influence individual working in companies and their responses to innovations (Jassawalla and Sashittal 2002;Uğur 2017). The amount of initial resistance generated and thus the probability that a mandated usage transforms into forced adoption might principally be much higher in countries like Greece with high uncertainty avoidance (Tsatsou 2012) compared to countries like Denmark with low uncertainty avoidance (Peters and Den Dulk 2003).…”
Section: Addressing Research Gaps Related To Boundary Conditionsmentioning
confidence: 99%
“…The findings of Kunze et al (2013) at least show that older employees were less resistant towards IT innovations than their younger colleagues. Similarly, differences in social and national culture were also shown to influence individual working in companies and their responses to innovations (Jassawalla and Sashittal 2002;Uğur 2017). The amount of initial resistance generated and thus the probability that a mandated usage transforms into forced adoption might principally be much higher in countries like Greece with high uncertainty avoidance (Tsatsou 2012) compared to countries like Denmark with low uncertainty avoidance (Peters and Den Dulk 2003).…”
Section: Addressing Research Gaps Related To Boundary Conditionsmentioning
confidence: 99%
“…In addition, most studies have focused on technology transfer into developed countries, with the common assumption that the technology will be suitable, without considering cultural and social values that influence acceptance. Several researchers have noted that cultural background plays an essential role in the acceptance and use of technology [23], [24].…”
Section: A E-health In Jordan As a Developing Countrymentioning
confidence: 99%
“…Moreover, it has been explained that users from different countries will have variations in culture. A distinctive national culture is expected to be able to explain differences in the adoption of technologies [23], [24]. Indeed, previous studies have revealed that technology acceptance models and theories may not be applicable to various cultures because they have generally been developed in developed countries.…”
Section: A E-health In Jordan As a Developing Countrymentioning
confidence: 99%
“…A country’s cultural values influence technology acceptance [ 13 ]. Although the TAM has been used extensively when studying information technology adoption in Western countries, researchers noted that the TAM was not valid when applied to other cultures [ 13 , 20 ]. The UTAUT model was tested in non-Western cultures such as in Saudi Arabia [ 21 ], India [ 22 ], and China as compared to the United States [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these models, Hofstede and Minkov [ 25 ] provided detailed guidelines to explain and measure cultural value differences applied to national culture. To date, these cultural dimensions have been the most commonly used variables for examining models cross-culturally [ 13 , 20 , 24 , 26 ]. McCoy et al [ 27 ] conducted a simple analysis of variance for each of Hofstede and Minkov’s [ 25 ] cultural dimensions measured at the individual level across 8 countries.…”
Section: Introductionmentioning
confidence: 99%